Prognostic impact of prior local therapy in castration-resistant prostate cancer. (24th February 2021) - Koura, Mikifumi; Shiota, Masaki; Ueda, Shohei; Matsumoto, Takashi; Kobayashi, Satoshi; Monji, Keisuke; Kashiwagi, Eiji; Takeuchi, Ario; Inokuchi, Junichi; Shiga, Ken-ichiro; Yokomizo, Akira; Eto, Masatoshi
Abstract: Objective: This study aimed to reveal the prognostic values of prior local therapy in first-line therapy using androgen receptor-axis targeting agents (abiraterone or enzalutamide) or docetaxel for castration-resistant prostate cancer (CRPC). Methods: The study included 303 patients treated with first-line therapy for non-metastatic and metastatic CRPC. The association between prior local therapy and therapeutic outcome including progression-free survival and overall survival was investigated by univariate and multivariate analyses as well as propensity score-matched analysis. Results: In univariate analysis, local prior therapy was associated with a lower risk of all-cause mortality (hazard ratio, 0.56, 95% confidence interval, 0.40–0.79; P = 0.0009). Overall survival, but not progression-free survival, was better among patients with prior local therapy compared with patients without prior local therapy even after multivariate analysis and propensity score-matched analysis. Conclusions: This study robustly indicated that prior local treatment was prognostic for overall survival among patients with CRPC. This finding is useful to predict patient prognosis in CRPC. Abstract : This study investigated the prognostic impact of prior local treatment, and robustly indicated that prior local treatment was prognostic for overall survival among patients with CRPC.